The conceptual and clinical problems of paraneoplastic syndrome in oncology and internal medicine - Bilynsky, B.T.; Dzhus, M.B.; Litvinyak, R.I. (Experimental Oncology, 2015)
Symptomatology of oncological diseases consists not only of local symptoms caused by the primary malignancy or its metastases, but also by general systemic signs that are not directly connected with the tumor. These symptoms are mostly associated with autoimmunity or endocrine influences. In many cases, the source of paraneoplastic syndromes (PNS) is unknown. Nearly 15% of oncological patients demonstrate these syndromes but it is diagnosed much more rarely. The survey of the numerous PNS is offered. The significance of the PNS differs for oncologists and other physicians who encounter it in their practice. The reason of those differences, as well as the connection between PNS and cancer toxicity is discussed. The experience of antitoxic therapy (hemosorption, lymphosorption, enterosorption) used in our clinic in the previous years is overviewed. Key Words: cancer, diagnosis, paraneoplastic syndromes, tumor toxicosis.